Analysis of production whiteleg shrimp (Litopenaeus vannamei) in Bireuen Regency, Aceh Province - Nur, T.M; Irfannur, Irfannur (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Whiteleg shrimp (Litopenaeus vannamei) is one of the most important commodities grown in Aceh Province, with one location in Bireuen Regency. This commodity is a local, domestic, and exportable food product. There is little information on the supply chain for whiteleg shrimp fisheries production in Bireuen Regency. The goal of this study is to investigate the supply chain and production value of whiteleg shrimp in Bireuen Regency. One of the right approach concepts to overcome the problem of meeting consumer demand is to determine the level of the fisheries base sector in a region. The study was done from February to April 2024. This study employed descriptive analysis as its method. The analysis method employed is location quotient (LQ) analysis. According to the study’s findings, the average LQ values for whiteleg shrimp (Litopenaeus vannamei) production in Bireuen Regency vary by sub-district between 2019 and 2023. The sub-districts of Sp Mamplam, Pandrah, Jeunieb, Plimbang, Jeumpa, and Peusangan are home to the LQ value category with the basic LQ value. The sub-districts of Samalanga, Peudada, Kuala, Jangka, Kuta Blang, and Gandapura are home to the LQ value category in the non-base category. The Jangka sub-district has the highest production value of whiteleg shrimp, namely from 2019 to 2023. In 2023, the highest production value of whiteleg shrimp is 4,452.80 tons.